INFLUENCE OF RANDOM NUMBER GENERATORS IN AIR POLLUTION MODEL SAMPLING - Vrglevski, G.; Mitreski, Kosta; Naumoski, Andreja; Zajkova, SG (Scientific Technical Union of Mechanical Engineering" Industry 4.0", 2018)
The research covers the usage of the random numbers in Monte Carlo simulations for air pollution models. Two new random number generators are developed; their strengths are compared with the existing random number generators. The results in this paper showed that the two newly developed random number generators achieved better results on a basis of failed test, however it extended the time for generating random numbers. In future we plan to use the newly developed random generators for filling the missing values in the measurements.
Keywords: Monte Carlo, Random Numbers, Ecology, Modeling, Random Generators